A myth in language teacher learning: Lesson observation - Gu, Min (Frontiers in Psychology, 2022)
This study explores the learning process of 32 Chinese senior high school EFL (English as a foreign language) teachers via three demonstration lessons. It was demonstrated via a data analysis of oral reports and interviews that the cognitive activity of “question”, which was considered as a significant contributor to collaborative discussion, was seldom involved in the participating teachers’ learning process, and that the absence of this cognitive activity reduced their learning to individual study of the observed practical skills. The study further reveals four factors that prevented the participating teachers from collaboratively constructing language teaching knowledge based on what was observed: These were (1) their perceived purpose of the modelled lessons, (2) their manner of making meaning, (3) their understanding of observer–observed relationship, and (4) their perception of professional learning. The analysis presented provides important insights for teacher educators to better facilitate in-service teachers of foreign languages learning through observation.